Effect of Current Ratio and Return on Equity on Dividend Payout Ratio Policy - Jati, Waluyo (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
The purpose of this study was to determine the effect of the current ratio and return on equity on dividend payout ratios in Manufacturing Companies Engaged in the Metal Industry Sector in the Indonesia Stock Exchange in 2014-2018. The method used in this study is associative, the sample used is the 5-year financial report that has made panel data. The analysis tool uses regression, coefficient of determination and hypothesis testing. The results of the study concluded that there was a significant effect between the current ratio to the dividend payout ratio with a determination of 35.4% and the hypothesis test of significance of 0,000 <0.05. There is a significant effect between return on equity on dividend payout ratio with a determination of 36.5% and the hypothesis test of significance 0,000 <0.05. There is a significant simultaneous effect between the current ratio and return on equity to the dividend payout ratio with a determination of 52.0% and the hypothesis test of significance 0,000 <0.05.